High-performance machine design for propulsion and on-board integrated battery charger for a heavy-duty commercial electric vehicle - Alwadie, Hatim (2024)
The adoption of four-wheel electric vehicles (EVs) in the automotive market has helped to alleviate the climate change issue. One of the most prominent but least explored areas is the electrification of trucks/lorries. Electrification of trucks has a vital role in achieving a cleaner environment as they consume more fuel than four-wheel passenger cars. Inherently having massive torque and power requirements along with huge field weakening range (four-five times base speed) makes this application extremely challenging and difficult to consider.